Analysis Of Grammatical Cohesion in Maudy Ayunda’s Buka Kartu Special Valentine’s Day: Conversation on Love - Syifa Ananda Putri; Ervina CM Simatupang (Universitas Nahdlatul Wathan Mataram, 2024)
Communication is an important thing especially for humans to give information to each other, and humans use conversation to convey something with the tool language. Discourse analysis as part of linguistics is the study of how language is spoken or written. In this research, the researcher analyzes the language spoken by Maudy Ayunda and Jessie Choi from one of Maudy’s videos on YouTube. People should make a good sentence in a conversation to make it easier to understand others. In conversation there are two or more people that talk to each other, it is a good conversation when they reply to each other. Another thing that makes a good sentence is grammatical cohesion which is part of discourse analysis. Grammatical cohesion is the study of how a component of grammar in a sentence is according to the rules. Grammatical cohesion has four types, there are conjunction, reference, ellipsis, and substitution. The theory of grammatical cohesion that the researcher uses is from Halliday and Hasan (1976) with the qualitative descriptive method to explain more detail about each type of grammatical cohesion. From 30 pieces of data that the researcher found in the conversation, there are 14 personal references, 5 additive conjunctions, 4 demonstrative references, 3 causal conjunctions, 2 verbal substitutions, 1 comparative reference, and 1 temporal conjunction. The most frequent grammatical cohesion in Maudy Ayunda’s video is personal references.